The Effect of Hypnoterapy Trauma Healing for Woman Victims of Sexual Violence on the Depression Scale in Tulungagung - Dini Eka Pripuspitasari; Ananingati Ananingati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Women Reproductive health has a continuous process and holistic problem. The fact is that 65% of indonesian women has a reproductive health problems. Bhayangkara Tulungagung Hospital regarding the ages of female victims of sexual violence varied between the ages of 4 to 57 years, with the distribution being children 15.2%, youth 51.5% and adults 33.3% (2017-2018). So far, the handling of cases of sexual violence against women has focused on providing legal action to the perpetrators of violence. Hypnotherapy techniques are expected to be a breakthrough in dealing with depressive conditions experienced by female adolescent victims of sexual violence. This research is a comparative observational study with a Two Groups Pretest with Control Group Design. The population in this study were all female adolescent victims of sexual violence who underwent post mortem et repertum at Bhayangkara Tulungagung Hospital in the period November 2018 to August 2019 as many as 20 female adolescents. The sampling method was carried out using a purposive sampling technique. Research data analysis was carried out using the Wilcoxon test. The results showed that there was a significant difference in the depression scale in the trauma healing hypnotherapy treatment class, with probability = 0.004 < α = 0.05. There were significant differences in the depression scale of female adolescent victims of sexual violence at Bhayangkara Tulungagung Hospital, with probability = 0.03 < α = 0.05. Adolescent who were victims of sexual violence who received hypnotherapy treatment had a lower depression scale compared to those who did not receive treatment. Traumatic healing hypnotherapy can affect the decrease in the depression scale in female adolescent victims of sexual violence at Bhayangkara Tulungagung Hospital.